Dakwah Bil Hal dalam Membina Narapidana di Palangka Raya - Mahriyani Mahriyani; Syairil Fadli (Syams, 2020)
This article aims to explain Da’wah Bil Hal  towards the Development of prisoners in the Class II A Palangka Raya Penitentiary. This research is a field study using a descriptive qualitative approach. Located in class IIA Correctional Institution Palangka Raya, Jl. Tjilik Riwut. Km 2.5, Jekan Raya District, Palangka Raya City, Central Kalimantan. Data collection was carried out by observation, interviews, documentation and literature study. This study found that the form of Da’wah Bil Hal in the development of prisoners carried out by the Palangka Raya class II A correctional facility, namely familiarizing with congregational prayer, group dhikr, tadarus, learning to write and read the Qur’an, worship practices, active mentor, exemplary and motivation. from prison officers, as well as encouragement from prison officers to inmates to participate in activities. Furthermore, coaching is based on two areas, namely personality development to change the character of the prisoner and self-reliance development to increase skills so that they become provisions for inmates to build independent businesses. Factors that support the success of coaching prisoners are adequate facilities, cooperation or kinship between prison officers and prisoners as well as the activeness and persistence of mentors in providing material or teaching. Meanwhile, the inhibiting factors include: prisoners, schedule, and time.Ali, Mukti, dan Saipullah Hasan. 2019. “Da’wah Bi al-Hal in Empowering Campus-Assisted Community through Waste Bank Management.” Ilmu Dakwah: Academic Journal for Homiletic Studies 13 (2): 201–19. https://doi.org/10.15575/idajhs.v13i2.6441.Aliyudin. 2016. “Dakwah Bi Al-Hal Melalui Pemberdayaan Ekonomi Masyarakat.” Anida (Aktualisasi Nuansa Ilmu Dakwah) 15 (2): 187–206. https://doi.org/10.15575/anida.v15i2.1168.Alkausarni. 2017. “Strategi Komunikasi Lembaga Pemasyarakatan dalam Merehabilitasi Pengguna Narkoba (Studi Kasus Lembaga Pemasyarakatan Kelas II A Banda Aceh).” Skripsi, Banda Aceh: UIN Ar-Raniry Banda Aceh. http://library.ar-raniry.ac.id.Anwar, Herles, dan Mualimin. 2019. “Dakwah Melalui Pembinaan Keagamaan Terhadap Masyarakat Muslim Pedalaman Oleh Penyuluh Agama Islam Non PNS Kecamatan Tebas, Sambas.” Jurnal Bimbingan Penyuluhan Islam 1 (01): 23–36.Aziz, Moh Ali. 2009. Ilmu Dakwah. Jakarta: Kencana.“Data Terakhir Jumlah Penghuni Per-UPT pada Kanwil.” 2020. 2020. http://smslap.ditjenpas.go.id/public/grl/current/daily/kanwil/db653780-6bd1-1bd1-fbec-313134333039/date/2020-06-16.Dianto, Icol. 2018. “Peranan Dakwah Dalam Proses Pengembangan Masyarakat Islam.” Hikmah 12 (1): 98–118. https://doi.org/10.24952/hik.v12i1.854.Handayani, Iin. 2019. “Konsep Bimbingan dan Konseling Pribadi-Sosial dalam Pengembangan Positive Mental Attitude Generasi Z.” NALAR: Jurnal Peradaban dan Pemikiran Islam 3 (1): 51–63. https://doi.org/10.23971/njppi.v3i1.1283.Khair, Nurul, dan Muhammad Thaha. 2020. “Treating Religious Differences: Hikmah Muta’aliyah as An Alternative to Ethical Crisis in Contemporary Era.” NALAR: Jurnal Peradaban Dan Pemikiran Islam 4 (1): 1–18. https://doi.org/10.23971/njppi.v4i1.1928.Kurniawan, Asep. 2017. “Bil Hal Penciptaan Budaya Agama Melalui Pembiasakan Shalat Berjamaah Di Sekolah Menengah Pertama Islam Al-Azhar 5 Kota Cirebon.” ORASI: Jurnal Dakwah Dan Komunikasi 8 (1): 50–67. https://doi.org/10.24235/orasi.v8i1.2016.Mualimin. 2020. “Makan Besaprah: Pesan Dakwah Dalam Bingkai Tradisi Pada Masyarakat Melayu Sambas, Kalimantan Barat.” Ath Thariq Jurnal Dakwah Dan Komunikasi 4 (1): 1–19. https://doi.org/10.32332/ath_thariq.v4i1.2017.Nugrahani, Farida. 2014. Metode Penelitian Kualitatif dalam Penelitian Pendidikan Bahasa. Solo: Cakra Books.Nurjanah, Siti. 2020. “Pembentukan Akhlak Berbasis Pembiasakan Dan Keteladanan (Studi Kasus Di MAN 2 Kuningan Jawa Barat).” Oasis : Jurnal Ilmiah Kajian Islam 4 (2): 55–72.Puspitasari, Gesti, Misyuraidah Misyuraidah, Muhammad Fauzi, dan Syarnubi Syarnubi. 2019. “Pembinaan Keagamaan Peserta Didik Muslim Oleh Guru Pendidikan Agama Islam (PAI) Di Yayasan Khatolik.” Jurnal PAI Raden Fatah 1 (4): 497–508. https://doi.org/10.19109/pairf.v1i4.3595.Qonitah, Niswah. 2020. “Eksistensi Peradaban Islam pada Masa Dinasti Ilkhan Pasca Invasi Mongol.” NALAR: Jurnal Peradaban dan Pemikiran Islam 4 (1): 19–28. https://doi.org/10.23971/njppi.v4i1.1897.Sabila, Nur Akhda. 2019. “Integrasi Aqidah Dan Akhlak (Telaah Atas Pemikiran Al-Ghazali).” NALAR: Jurnal Peradaban dan Pemikiran Islam 3 (2): 74–83. https://doi.org/10.23971/njppi.v3i2.1211.Sagir, Akhmad. 2015. “Dakwah Bil-Hal: Prospek Dan Tantangan Da’i.” Alhadharah: Jurnal Ilmu Dakwah 14 (27): 1–13. https://doi.org/10.18592/alhadharah.v14i27.1224.Sulaiman, Ahmad, Supriyantho Supriyantho, dan Fantika Febry Puspitasari. 2019. “Islam Dan Pembebasan: Elemen-Elemen Teologis Dalam Menciptakan Transformasi Sosial.” NALAR: Jurnal Peradaban Dan Pemikiran Islam 3 (2): 112–21. https://doi.org/10.23971/njppi.v3i2.1478.